Peran Program Sehari Berbudaya Pasti Aceh(SEDATI) Dalam Upaya Melestarikan Kearifan Budaya Lokal Di SD Negeri 53 Banda Aceh - Linda, Roslinda; Julia, Putry; Maksum, Hafidh (UNIB Press, 2024)
This research aims to determine the role of the Definite Aceh Culture Day (SEDATI) program in efforts to preserve local cultural wisdom at SD Negeri 53 Banda Aceh. This program is a policy launched by the Banda Aceh city government through the education and culture department (Disdikbud) to introduce Aceh's local cultural wisdom to students from an early age. This study used descriptive qualitative method. The subjects in this research were school principals, teachers and students. Data collection techniques were carried out by conducting observations and interviews. The results of the research show that the One Day with Definitely Acehnese Culture (SEDATI) program is effective in increasing students' understanding and appreciation of Acehnese culture. Additionally, this program strengthens identity and pride among students. In conclusion, the Pasti Aceh Culture Day program has made a significant contribution to preserving local cultural wisdom in the elementary school environment and can be a model for similar initiatives in other areas